Autonomous Cooperative Control for Hybrid AC/DC Microgrids Considering Multi-Energy Complementarity - Zhou, Dan; Chen, Shangren; Wang, Hanyun; Guan, Minyuan; Zhou, Lihua; Wu, Jian; Hu, Yaojie (Frontiers in Energy Research, 2021)
Multi-energy hybrid AC/DC microgrids (MGs), considering ice storage systems (ISSs), can promote the flexible integration and efficient utilization of distributed generators (DGs) and energy storage systems (ESSs), provide a reliable power supply for local loads, and achieve multi-energy complementarity and energy savings at the same time. An autonomous cooperative control of multi-energy MGs is proposed in this paper, which can realize the following targets: 1) In the energy storage period, ice storage systems and energy storage systems can absorb energy in accordance with their rated capacity. 2) In the energy releasing period, ice storage systems are first put into operation, and the rest of the equivalent cooling loads and electrical loads are shared by the energy storage systems according to their rated capacity ratio. Besides, the complete system small signal model is constructed, which can be used to analyze the features and characteristics of the system and guide the optimal design of the control parameters. Finally, the effectiveness of the proposed control is corroborated by several case studies conducted in PSCAD/EMTDC.